A principle-based approach to the design of a graduate resilience curriculum framework. Issue 4 (7th June 2022) - van Kessel, Gisela; Brewer, Margo; Lane, Murray; Cooper, Berni; Naumann, Fiona
ABSTRACT: This article describes the principles and structure used to create the Graduate Resilience Curriculum Framework intended to support academics to develop higher education students' resilience as an important graduate attribute. Enhancing student resilience requires a structured approach to learning that articulates the factors that are important for the building of resilience, in a format that reflects incremental development across the student journey. This paper describes the principles used to inform the design and development of the curriculum framework including the adoption of a systemic program approach that is strengths-based, learner-centred and viewed through an ecological lens to support students' resilience over time. The three learning domains of knowledge, skills and application guide students to develop a sense of themselves as resilient. The Graduate Resilience Curriculum Framework provides an evidence-based guide for university staff to embed strategies that develop student resilience in a planned, supportive and scaffolded way.